On essential and continuous spectra of the linearized water-wave problem in a finite pond - Nazarov, Sergey A.; Taskinen, Jari (MATHEMATICA SCANDINAVICA, 2010)
We show that the spectrum of the Laplace equation with the Steklov spectral boundary condition, in the connection of the linearized theory of water-waves, can have a nontrivial essential component even in case of a bounded basin with a horizontal water surface. The appearance of the essential spectrum is caused by the boundary irregularities of the type of a rotational cusp or a cuspidal edge. In a previous paper the authors have proven a similar result for the Steklov spectral problem in a bounded domain with a sharp peak.